(untitled) (Annals of Medical Research, 2021)
Aim: In this study, we aimed to evaluate the effect of the use of the oral polytendon complex (Tendoflex Mega-Farma Pharmaceutical Company) as a nutritional supplement after the open repair of Achilles tendon rupture cases on clinical outcomes.Material and Methods: This study included 29 consecutive patients with Achilles tendon ruptures who had undergone open repair of the Achilles tendon and took postoperative oral Tendoflex treatment as a dietary supplement. Patients have been followed up in the postoperative 8th 12th and 48th weeks. The ranges of motions and visual analog scale (VAS) score for pain was noted. The Achilles tendon Total Rupture Score(ATRS) was also pointed out at the last follow up.Results: There were no cases of re-rupture. There were no cases of infection and or nerve injury. 48th week follow up results were plantar flexion 47.1 degrees, dorsiflexion 17.8 degrees, eversion 17.1degrees, inversion 28.2 degrees with a mean VAS score of 0.6 and a mean ATRS of 93.Conclusion: The open repair of Achilles tendon ruptures has certain advantages like lower re-rupture rates and lower iatrogenic neural injury rates. Including Tendoflex to the treatment protocol, may also have prevented re-ruptures and provided rapid amelioration of pain.